The Influence of Resilience and Mathematical Literacy on Students' Mathematical Problem Solving Abilities - Nurlaeli Khalidah; Dian Nopitasari; Rika Sukmawati (Universitas Suryakancana, 2026)
Mathematics learning in schools is often viewed as a mechanical process that emphasizes memorizing formulas, resulting in students being less able to relate concepts to real-world situations and experiencing difficulties in solving non-routine problems. This condition demands strong resilience and mathematical literacy skills so that students can survive, adapt, and think flexibly when facing problems. This study was conducted to analyze the influence of resilience and mathematical literacy on the ability of junior high school students to solve mathematical problems. The method used is a quantitative correlational study with a population of all seventh grade students of SMPN 27 Kota Tangerang in the 2025/2026 academic year and a sample of 36 students selected through cluster random sampling. Data in this study were obtained through resilience and mathematical literacy questionnaires and mathematical problem solving ability tests. All instruments have undergone validity and reliability tests before use. Data analysis using multiple linear regression with the help of SPSS version 29. The results showed that resilience significantly influenced students' mathematical problem solving abilities, while mathematical literacy did not. Simultaneously, resilience and mathematical literacy have not shown a significant influence on students' mathematical problem solving abilities. The coefficient of determination of 15.5% indicates that mathematical problem solving ability is influenced by resilience and mathematical literacy, while the remaining is influenced by other factors outside the research. Thus, resilience is a crucial factor that needs to be developed in mathematics learning to support students' mathematical problem solving abilities.